Barriers and Facilitators of Community-Based Health Insurance Membership in Rural Amhara Region, Northwest Ethiopia: A Qualitative Study - Demissie GD; Atnafu A (Dove Medical Press, 2021)
Getu Debalkie Demissie,1 Asmamaw Atnafu2 1Department of Health Education and Behavioral Sciences, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Getu Debalkie Demissie Email getud2006@gmail.comBackground: More than 150 million people encounter huge cost of health expenses every year, and most of these treatment seekers face poverty owing to out-of-pocket payments. Community-based health insurance (CBHI) won popularity as a makeshift health financing mechanism for out-of-pocket payments in poor communities. The aim of this study was therefore to explore the facilitators and impediments of enrollment to community-based health insurance in rural parts of the Amhara region, Ethiopia.Methods: Focus Group Discussion (FGD) was the main data collection instrument supplemented by key informant interview (KII). The FGD participants were selected using a purposive sampling technique. The participants were therefore selected based on their membership status of CBHI (members or non-members). Six FGDs and four KIIs were conducted in November 2019 in three districts. Before analyzing the data, all FGDs and KIIs were transcribed and transferred into ATLAS.ti version 7.1 software. An inductive thematic analysis approach was done, that is, on the basis of major themes emerged from the data.Results: Low level of awareness, perception of high amount of premium, poor perception of quality of services and lack of trust are the barriers to join community-based health insurance.Conclusion: There has been low level of awareness and misconception about community-based health insurance. The major reason to decline to join CBHI was low capacity to pay the premium.Keywords: community-based health insurance, enrolment, Ethiopia